PERBEDAAN KADAR HEMOGLOBIN (Hb) dan INDEKS ERITROSIT SEBELUM DAN SESUDAH MENGONSUMSI TABLET TAMBAH DARAH (TTD) PADA REMAJA PUTRI ANEMIA - Rumeyda Chitra Puspita Puspita; Lucia Sincu Gunawan; Dhiana Puspitasari; Adelya Althaf Anggraini (LPPM Universitas Abdurrab, 2025)
Anemia is a global health problem frequently affecting adolescent girls, characterized by hemoglobin levels below normal. The main causes of anemia include inadequate iron intake and unhealthy lifestyle habits. This study aimed to determine the differences in hemoglobin levels and erythrocyte indices (MCV, MCH, MCHC) before and after consuming iron tablets among anemic adolescent girls. This research employed a quasi-experimental design with a one-group pretest-posttest conducted in April–May 2025. The subjects were 28 female students of Setia Budi University selected using purposive sampling. Data collection included laboratory examination of hemoglobin and erythrocyte indices as well as questionnaire responses. The intervention consisted of daily iron tablet supplementation for 20 days. The results showed that the median hemoglobin level increased from 11.1 g/dL (10.3–11.7) to 11.6 g/dL (10.8–12.1). The Wilcoxon Signed Rank Test indicated a significant difference in hemoglobin levels before and after supplementation (p < 0.001). Erythrocyte indices also improved, with mean MCV increasing from 74.03 ± 5.9 fL to 74.52 ± 7.6 fL, MCH from 22.76 ± 2.5 pg to 25.21 ± 3.1 pg, and MCHC from 30.77 ± 1.3% to 33.35 ± 2.4%. The paired t-test confirmed significant differences in MCV, MCH, and MCHC before and after iron tablet consumption. There were significant differences in hemoglobin levels and erythrocyte indices before and after iron tablet supplementation among anemic adolescent girls.